Kotak Amal Pintar Berbasis Internet of Things (IoT) Menggunakan Platform Blynk di SMAN 1 Serangpanjang - Soendara, Asep; Permana, Eka; Udoyono, Kodar; Aji, Setia; Muhajir, Akrom; Leander, Daud Elia (STMIK Subang, 2025)
The objective of this study is to develop an Internet of Things (IoT)-based donation box that can be monitored and controlled remotely through the Blynk platform. Conventional donation boxes typically rely on manual counting methods, which are prone to manipulation and errors, as well as vulnerabilities related to the use of traditional keys, such as loss or unauthorized duplication. To address these issues, this research proposes an IoT-enabled system designed to enhance both transparency and security. The research methodology includes a literature survey to understand IoT concepts and relevant technologies, as well as an evaluation of RFID readers and color sensors. Additionally, user requirements analysis and system design were conducted to ensure the accurate and relevant delivery of information. The expected outcome of this study is a prototype that enables real-time monitoring of donation box security, thereby improving reliability and safeguarding donations. Furthermore, this work is expected to serve as a reference for future research related to IoT-based security systems